How to enter the Church when the door is closed. Language policies in Christian churches of Joensuu in the context of a migrant's choice - Krihtova, Tatiana (International Journal of Contemporary Economics and Administrative Sciences, 2016)
<span style="background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="EN-US">The article describes how Christian churches in the Finnish city Joensuu chose language policies towards Russian-speaking migrants. The author carried out a fieldwork, using participant observation and auto ethnography approaches in all churches of the city. The preliminary hypothesis was that language policy in churches (translation of worship, ability to study Bible, informal talks) determinate religious choice of migrants which influence the strategies of adaptation in a new country. The church parishes have completely different approaches towards the communication with migrants, all described and compared in the article.